Specimen thickness dependence of large scale fiber bridging in mode I interlaminar fracture of carbon epoxy composite. (1st March 2015) - Farmand-Ashtiani, E.; Cugnoni, J.; Botsis, J.
Abstract: Large scale bridging is an important toughening mechanism in composite laminates that depends on the specimen geometry as well as the constituent materials. In this work, an iterative approach is applied to identify the effect of specimen thickness on traction–separation behavior in the bridging zone. Double cantilever beam specimens (DCB) with embedded arrays of wavelength-multiplexed fiber Bragg grating (FBG) sensors are subjected to monotonic mode I fracture loading. As processed specimens with thicknesses h  = 2, 4, 8 and 10 mm as well as specimens of h  = 4 mm milled down from the 8 and 10 mm are tested. Non-homogeneous strain distributions in the vicinity of the interlaminar crack plane are locally monitored by means of embedded FBGs. The measured strain data are used to quantify the bridging tractions associated with each specimen thickness and consequently the energy release rate (ERR) due to the bridging. The results show that the bridging zone length and the ERR at the plateau level increase with specimen thickness while the results for all specimens with h  = 4 are the same thus excluding any processing effects. Moreover, the maximum stress of traction-opening in the bridging zone and crack opening displacement at the end of the zone are independent of thickness. In contrast, the rate of tractions decay depends on the specimen thickness in that it decreases with thickness scaling. Thus the so-called bridging law is not a material parameter. The identified traction–separation relations are employed in a cohesive zone model to predict fracture of DCB specimens with different thicknesses.